Comparison of the Pipeline embolisation device alone or combined with coiling for treatment of different sizes of intracranial aneurysms. Issue 4 (6th April 2022) - Wang, Chao; Luo, Bin; Li, Tianxiao; Maimaitili, Aisha; Mao, Guohua; Song, Donglei; Wang, Yunyan; Feng, Wenfeng; Wang, Yang; Shi, Huaizhang; Wan, Jieqing; Liu, Jianmin; et al.
Abstract : Objectives: The aim of this study was to compare complications and outcomes between intracranial aneurysms treated with the Pipeline embolisation device (PED) alone or with PED combined with coiling for different-sized aneurysms. Method: Patients with aneurysms treated by PED were collected from the PED in China postmarket multicentre registry study. We performed a propensity match analysis to compare the efficacy and safety between PED alone and PED combined with coiling treatment, and then aneurysms were organised into three groups based on their size: small (≤7 mm), medium (≤15 mm to >7 mm) and large/giant (>15 mm). Complications and aneurysm occlusion rates in the aneurysm size groups were compared between PED alone and PED combined with coiling patients. Result: A total of 1171 patients with 1322 aneurysms were included. All patients received clinical follow-up, while angiographic follow-up was available in 967 aneurysms. For small aneurysms, there was no difference in the aneurysm occlusion rate between two groups (79.1% vs 88.4%, respectively), while there was a significant increase in the ischaemic complication rate (8.3% vs 19.3%, respectively, p=0.0001). For medium and large/giant saccular aneurysms, PED combined with coiling significantly improved the occlusion rate (medium aneurysms: 74.7% vs 88.8%, respectively, p<0.0001; large/giant saccular aneurysms: 72.9% vs 86.9%, respectively, p=0.018), while there were no differences in the total complication rate. For large/giant non-saccular aneurysms, two groups showed no differences. Conclusion: Use of the PED with adjunctive coils can significantly improve the occlusion rate of medium aneurysms, without increasing the total complication rate.